2020
DOI: 10.3389/fped.2020.00586
|View full text |Cite
|
Sign up to set email alerts
|

Profiling FLT3 Mutations in Mexican Acute Myeloid Leukemia Pediatric Patients: Impact on Overall Survival

Abstract: Background: Acute myeloid leukemia (AML) is the second most frequent leukemia in childhood. The FLT3 gene participates in hematopoietic stem cell proliferation. FLT3 mutations are recurrent in AML and influence prognosis. In Mexican pediatric AML patients, FLT3 mutational profile, and their clinical impact have not been evaluated. Aim of the study: This study aimed to identify the profile of FLT3 mutations in pediatric patients with de novo AML and to assess their possible influence on overall survival (OS) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…Demographic, clinical, and the main biological characteristics of the patients were previously reported ( 17 ). Fifty-five percent of the patients were male.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Demographic, clinical, and the main biological characteristics of the patients were previously reported ( 17 ). Fifty-five percent of the patients were male.…”
Section: Resultsmentioning
confidence: 99%
“…Data were collected from medical charts, including sex, age, peripheral white blood cell count, percentage of bone marrow blasts at diagnosis, FAB (French-American-British) classification, and treatment protocol. The clinical features of the analyzed patients had been previously reported in Molina et al ( 17 ).…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Similar relationships were observed also in some previous studies 16 , 29 , 34 . Moreover, Molina Garay et al demonstrated that patients with the FLT3 -ITD mutation characterized with significantly shorter lifespan as compared to patients lacking the FLT3 -ITD mutation or with a mutation in the tyrosine kinase domain ( FLT3 -TKD) 36 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, mutations in FLT3-ITD, DNMT3A, NPM1 , and IDH2 were underrepresented in Hispanics ( Gomez-Arteaga et al 2020 ). However, mutated FLT3 was recently shown to have a negative impact on outcomes in Mexican children ( Molina Garay et al 2020 ).…”
Section: Acute Leukemiasmentioning
confidence: 99%